Levosimendan improves cardiac function and myocardial efficiency in rats with right ventricular failure - Mona S. Hansen (Pulmonary Circulation, 2017)
Levosimendan is an inotropic and vasodilator drug, which is known to improve cardiac function in animal models of right ventricular (RV) failure. The effects of levosimendan on oxygen consumption and myocardial efficiency in the failing RV is unknown. We investigated the effects of levosimendan on RV function, myocardial oxygen consumption, myocardial external efficiency (MEE), and myocardial metabolism in rats with RV hypertrophy and failure. RV hypertrophy and failure were induced by pulmonary trunk banding in rats. Rats were randomized to seven weeks of treatment with vehicle (n = 16) or levosimendan (3 mg/kg/day) (n = 13). Control animals without pulmonary banding received vehicle treatment (n = 11). RV MEE and RV metabolism were evaluated by echocardiography, 11 C-acetate positron emission tomography (PET), 18 F-FDG PET, and invasive pressure measurements. We found that levosimendan improved RV MEE (26 ± 3 vs. 14 ± 1%, P  < 0.01) by increasing RV external work (0.62 ± 0.06 vs. 0.30 ± 0.03 mmHgċmL, P  < 0.001) without affecting RV myocardial oxygen consumption ( P  = 0.64). The improvement in RV MEE was not associated with a change in RV myocardial glucose uptake (1.3 ± 0.1 vs. 1.0 ± 0.1 µmol/g/min, P  = 0.44). In conclusion, in the hypertrophic and failing RV of the rat, levosimendan improves RV function without increasing myocardial oxygen consumption leading to improved MEE. The improvement in RV MEE was not associated with a change in myocardial glucose uptake. This study emphasizes the potential therapeutic value of chronic levosimendan treatment RV failure. It extends previous observations on the effect profile of levosimendan and motivates clinical testing of levosimendan in RV failure.